2007
DOI: 10.1001/archinte.167.22.2490
|View full text |Cite
|
Sign up to set email alerts
|

Association of Kidney Function and Albuminuria With Cardiovascular Mortality in Older vs Younger Individuals

Abstract: Background:The cardiovascular risk implications of a combined assessment of reduced kidney function and microalbuminuria are unknown. In elderly persons, traditional cardiovascular risk factors are less predictive, and measures of end organ damage, such as kidney disease, may be needed for improved cardiovascular mortality risk stratification.Methods: The glomerular filtration rate was estimated from calibrated serum creatinine, and the urine albumincreatinine ratio (ACR) was measured in 3 urine samples in 970… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
175
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(195 citation statements)
references
References 40 publications
17
175
0
3
Order By: Relevance
“…In contrast, reduced eGFR was a high risk for developing cardiovascular endpoints (cardiovascular death, new admissions due to to angina, myocardial infarction, stroke, revascularization or heart failure) and all-cause mortality independent of UACR [15]. Interestingly, the Second Nord-Trøndelag Health (HUNT II) study [16] reported that reduced eGFR with higher UACR was associated with a higher risk for cardiovascular events. This discrepancy compared to our present study may be partly because the number of patients with cardiovascular events in the present study was relatively small as shown in Table 2.…”
Section: \0001mentioning
confidence: 99%
“…In contrast, reduced eGFR was a high risk for developing cardiovascular endpoints (cardiovascular death, new admissions due to to angina, myocardial infarction, stroke, revascularization or heart failure) and all-cause mortality independent of UACR [15]. Interestingly, the Second Nord-Trøndelag Health (HUNT II) study [16] reported that reduced eGFR with higher UACR was associated with a higher risk for cardiovascular events. This discrepancy compared to our present study may be partly because the number of patients with cardiovascular events in the present study was relatively small as shown in Table 2.…”
Section: \0001mentioning
confidence: 99%
“…[33][34][35] Albuminuria is subject to large within-individual variations, with reported coefficient of variation of 50%, 36 and the conclusion as to whether microalbuminuria is present should preferably be based on repeated measurements. On the other hand, RI evaluation is easier because the same probe is used for the heart, and it causes little physical stress to patients.…”
Section: Discussionmentioning
confidence: 99%
“…with poor outcomes in this patient population (19,20). Unlike individuals who may never experience sequelae of their kidney disease, namely individuals with CKD defined solely by albuminuria and elderly patients with decreased eGFR from "natural aging" (21,22), patients who exhibit complications from their renal dysfunction may particularly benefit from being aware of their CKD.…”
Section: Discussionmentioning
confidence: 99%